2017
DOI: 10.1002/mbo3.451
|View full text |Cite
|
Sign up to set email alerts
|

Ribose operon repressor (RbsR) contributes to the adhesion of Aeromonas hydrophila to Anguilla japonica mucus

Abstract: The characterization of adhesion between pathogenic bacteria and the host is critical. Pathogenic Aeromonas hydrophila was shown to adhere in vitro to the mucus of Anguilla japonica. To further investigate the adhesion mechanisms of A. hydrophila, a mini‐Tn10 transposon mutagenesis system was used to generate an insertion mutant library by cell conjugation. Seven mutants that were impaired in adhesion to mucus were selected out of 332 individual colonies, and mutant M196 was the most severely impaired strain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Aeromonas hydrophila belongs to the Aeromonadaceae family (Lin et al, ) that is widely distributed in aquatic environment (Daskalov, ; Li et al, ; Xiong et al, ). It is regarded as one of the important pathogens in freshwater cultured animals (Abdolnabi, Ina‐Salwany, Daud, Mariana, & Abdelhadi, ; Baumgartner, Ford, & Hanson, ; Zhang et al, ) and has caused serious economic losses to the global aquaculture industry (Fang, Ge, & Sin, ; Hu et al, ; Ni, Wang, Liu, & Lu, ; Pridgeon et al, ; Zhang, Yan, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Aeromonas hydrophila belongs to the Aeromonadaceae family (Lin et al, ) that is widely distributed in aquatic environment (Daskalov, ; Li et al, ; Xiong et al, ). It is regarded as one of the important pathogens in freshwater cultured animals (Abdolnabi, Ina‐Salwany, Daud, Mariana, & Abdelhadi, ; Baumgartner, Ford, & Hanson, ; Zhang et al, ) and has caused serious economic losses to the global aquaculture industry (Fang, Ge, & Sin, ; Hu et al, ; Ni, Wang, Liu, & Lu, ; Pridgeon et al, ; Zhang, Yan, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion of the pathogen to the host surface constitutes a critical step in infection initiation (Chen et al., ; Shoemaker, LaFrentz, Peatman, & Beck, ), and multiple pathogenic bacteria show strong adhesion abilities (Lin et al., ; Papadopoulou, Dalsgaard, Lindén, & Wiklund, ; Qin, Lin, Chen, Xu, & Yan, ). Bacterial adhesion is regulated by different genes (Guo et al., ; Huang, Qin, et al., ; Jiang et al., ; Xu, Huang, Su, & Yan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Host mucus is abundantly found on the surface of the skin, gills, and gut lining; therefore, it is the first site of interaction between the pathogen and its host (Yan, Zhao, Wang, Zou, & Chen, 2010). Several genes have been demonstrated to be involved into the bacterial adhesion to fish mucus (Qin, Yan, Su, Li, & Zou, 2013;Qin et al, 2014;Qin, Lin, Chen, Xu, & Yan, 2016;Huang, Hu, et al, 2016;Huang et al, 2017;Lin et al, 2017). Previous researches on other bacteria have also shown that some secretion systems are necessary for adhesion, mainly through regulating the secretion of adhesin.…”
Section: Discussionmentioning
confidence: 99%